2017
DOI: 10.4025/actascianimsci.v39i3.34813
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effect of dietary probiotic supplementation on carcass traits and haematological responses of broiler chickens fed shea butter cake based diets

Abstract: ABSTRACT.A 42-day study was conducted to investigate probiotic supplementation on shea butter cake (SBC) based diets of broilers on the carcass traits and haematological indices. A total of 280, 1-day old Arbor acres strain broiler chicks were divided into 7 dietary treatments with 4 replicates of 10 birds each in a completely randomized design. Diet 1 (control diet) has no SBC and probiotic supplementation while remaining 6 diets contained 5, 10, and 15% levels of SBC each with (+) or without (-) probiotic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
2
5
1
Order By: Relevance
“…The drumsticks percentage of live weight among various treatments and main components (SCP level and protein source) were non-significant (p>0.05) across all diets. This is different from work by Aguihe et al [4041] who observed significant (p<0.05) effect on drumstick in birds fed with probiotic (0.5%)-SBC diets. The abdominal fat percentage of live weight were found comparable (p>0.05) among various treatments and main components (SCP level and protein source) which is similar to findings of Overland et al [3637].…”
Section: A C C E P T E D a R T I C L Econtrasting
confidence: 99%
See 1 more Smart Citation
“…The drumsticks percentage of live weight among various treatments and main components (SCP level and protein source) were non-significant (p>0.05) across all diets. This is different from work by Aguihe et al [4041] who observed significant (p<0.05) effect on drumstick in birds fed with probiotic (0.5%)-SBC diets. The abdominal fat percentage of live weight were found comparable (p>0.05) among various treatments and main components (SCP level and protein source) which is similar to findings of Overland et al [3637].…”
Section: A C C E P T E D a R T I C L Econtrasting
confidence: 99%
“…The broilers fed with 7.5 and 10% SCP incorporated diets showed significantly (p<0.01) increased thigh percentage. The results are in accordance with Aguihe et al [4041] observed significant (p<0.05) effect on thigh in birds fed probiotic (0.5%)…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 92%
“…The higher carcass weight and breast yield observed in the LAB supplemented groups is attributed to higher BWG in the ducks of these groups. These carcass improvements could be due to their ability to enhance the bioavailability of nutrients and increase digestive enzymes thereby promoting the growth of muscle tissues (Aguihe et al 2017). Improvements in carcass and breast yield were also noted in broiler chicken after supplementing probiotic LAB (Salehizadeh et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, supplementation with probiotics for diets containing significant amounts of TA may mitigate the adverse effects of the ingested TA. This improvement could be due to the cumulative effects of the probiotic microbes, which include higher digestive enzyme activity and neutralization of the effect of feed toxins in the gut environment in broiler chickens [ 50 , 51 , 52 , 53 , 54 ]. Probiotics consisting of B. mesenteric , C. butyricum , and S. faecalis could prevent the growth of E. coli , which is deleterious to the intestines of infant rabbits [ 55 ].…”
Section: Discussionmentioning
confidence: 99%